PRINSIP PENDIDIKAN AGAMA ISLAM DALAM MEWUJUDKAN KESEHATAN MENTAL DAN GOOD GOVERNMENT - Muhamad Fatihul Afham (JURNAL INDO-ISLAMIKA, 2018)
This study aims to determine the principles of Islamic religious education in realizing mental health, as well as the role of Islamic education in creating good government. This study uses a qualitative approach with library research methods (literature study). Collecting data using documentation techniques. The data analysis used descriptive analysis techniques.The results showed that religion is an important element in mental development. Without religion, development plans will not be carried out properly. Because a person can carry out his plans properly depending on the calm of his soul. If his soul is restless he will not be able to deal with the problems inherent in implementing these plans. A mentality that grows without religion will not necessarily be able to achieve integrity due to a lack of peace and tranquility of the soul.Islamic Religious Education is education based on the teachings of the Islamic religion, namely in the form of guidance, care for students, so that later after completing education, they can understand, live and practice the teachings of Islam as a way of life for the sake of safety and welfare of life in this world and in the hereafter. Thus, if Islamic religious education can become a way of life for each individual, then mental health and goo govermunt will automatically be realized.